2016
DOI: 10.1016/j.jplph.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting ethylene and carbon dioxide concentrations during ripening: Incidence on final dry matter, total soluble solids content and acidity of mango fruit

Abstract: Ripening of climacteric fruits is associated with pronounced changes in fruit gas composition caused by a concomitant rise in respiration and ethylene production. There is a discrepancy in the literature since some authors reported that changes in fruit gas compositions differ in attached and detached fruits. This study presents for the first time an overview of pre- and post-harvest factors that lead to variations in the climacteric respiration and ethylene production, and attempts to determine their impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 88 publications
4
12
0
1
Order By: Relevance
“…The titratable acidity of fruits subjected to 240-min fast cooling decreased after 14 days of cold storage and reached stability after three days of shelf-life. Acidity decreased due to the oxidative degradation of citric acid, which is an organic substance essential for energy production during respiration of fruits in storage (Chitarra & Chitarra, 2005;Emongor, 2015;Nordey et al, 2016;Lawson et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The titratable acidity of fruits subjected to 240-min fast cooling decreased after 14 days of cold storage and reached stability after three days of shelf-life. Acidity decreased due to the oxidative degradation of citric acid, which is an organic substance essential for energy production during respiration of fruits in storage (Chitarra & Chitarra, 2005;Emongor, 2015;Nordey et al, 2016;Lawson et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The advanced stages of ripening impacted the absence of significant differences in the quality parameters. Most cellular metabolic activities related to texture, pigment deposition, acidity changes, sugar conversion, and production of aromatic volatile chemical compounds were stabilized (Goulao & Oliveira, 2008;Mossad et al, 2016;Nordey et al, 2016). Rapid cooling programs and cold storage kept reduced water loss and extended fruit shelf life (Brosnan & Sun, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Although TSS content represents carbohydrates, organic acids, proteins, fats and minerals, changes in TSS during fruit ripening are mainly associated with the increase alteration of carbohydrate to simple sugars [44]. Nordey et al [45] reported the TSS content increased~2-folds during the process of ripening in mango fruits. The TSS of all mango varieties was between 10.7-11.6 Brix in which glucose, fructose and sucrose constituted the majority of carbohydrates [39].…”
Section: Plos Onementioning
confidence: 99%